WORKFLAGE: uma ferramenta de definição e criação de Workflow baseado em agentes de software para WEICOT - Fialho, Hugo Sampaio (2003)
The Workflow Management Systems (WfMS) have been used in many organizations with the objective of reducing, improve and control the workflow in their internal process. Current WfMS are, usually, designed to the administration of loosely structured businesses process, where the logical flow of the tasks totally predefined. However, not all business processess are like this. With the coming of the new communication technologies among the 6 organizations, the business environment becoming more and more dynamic demanding more complex processes. Considering this scenario, existent WfMS have some disadvantages and limitations and need improvements and modifications. Many researchers have been exploring the power of software agent's technology to provide solutions for current WfMS. There are several approaches, some are improvements with agents, another are based on agents. In this work we present the WorkFlage as a tool for the development Workflow Management Systems based on to technologies of Software Agents for the model proposed by the project WEICOT. The work is organized in 9 chapters where we cover from the technology of Workflow, going through a summary of the agents' technology, the state of the art in workflow based on agents, to case stud y of materials purchase where we demonstrate the application of the WorkFlage tool. At the end of this work we will make some final considerations where we propose improvements and suggestions for future works.